Geo: A Visual Analytics Tool for Spatiotemporal Analysis - Queiroz Neto, José F. de; Macêdo, José Antônio F. de; Trentini, Erick L.; Chaves, Samir B.; Castelo Branco, João Araújo (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
This paper presents Geo, a spatiotemporal analysis tool designed to support criminal analysis tasks such as hotspot detection and police patrol route planning. The system addresses the gap between traditional hotspot mapping and actionable patrol deployment by combining three techniques: MSKDE for high-resolution density estimation, SHOC for intuitive temporal comparison of crime hotspots, and HotSee for generating patrol routes along high-risk street segments. Through a real case study on robbery incidents in Vila Sônia, São Paulo, the paper demonstrates how Geo enables analysts to identify spatial and temporal crime patterns, adapt analysis to street networks, and create operational patrol routes. The results highlight Geo’s effectiveness in bridging strategic crime mapping and tactical decision-making, with future work aimed at real-time data integration and broader applications in public safety.